Health and medicine in the Islamic tradition based on the book of Medicine (kitab al-tibb) of Sahih al- Bukhari - Deuraseh, Nurdeng@Nurdeen (International Society for the History of Islamic Medicine, 2006)
This article attempts to study the book of medicine (kitab al-tibb) in Sahih al-Bukhari. The book of medicine appears in the book 76 which consists of 58 chapters with 105 traditions (hadiths). The titles of each chapter in the book of medicine reflect the content of traditions regarding the medicine and what is related to it. The book of Medicine (kitab al-tibb) gives primarily idea on the conditions of Muslims in the time of Prophet (s.a.w), how did they prevent and treat the disease. It is found that most of al-tibb al-nabawi is preventive medicine (al-tibb al-wiqa`i) rather than therapeutic medicine (al-tibb al-`ilaji), and has been practiced in the time of the Prophet (s.a.w) and even after.